Lipid and immune dysregulation and risk of metabolic disorders after HCV clearance in HIV/HCV-coinfected participants with cACLD: a retrospective study - Virseda-Berdices, Ana; Requena, Belen; Berenguer, Juan; González-García, Juan; Gonzalez-Riano, Carolina; Díez, Cristina; Hontañon, Victor; Fernández-Rodríguez, Amanda; Barbas, Coral; Resino, Salvador; Martín-Escolano, Rubén; Jiménez-Sousa, María Ángeles (Frontiers in Immunology, 2026)
IntroductionPeople with HIV and chronic hepatitis C may develop metabolic complications after sustained virologic response (SVR), possibly due to persistent molecular alterations induced by HCV. This study aimed to identify baseline (pre-treatment) lipid and immune biomarkers associated with post-SVR metabolic events in HIV/HCV-coinfected participants with compensated advanced chronic liver disease (cACLD) receiving long-term suppressive antiretroviral therapy.MethodsWe conducted a retrospective study of 56 HIV/HCV-coinfected participants with cACLD. Untargeted lipidomic profiling was performed on baseline plasma samples using a liquid-chromatography-mass spectrometer. The outcome was the development of metabolic events (diabetes mellitus and/or hyperlipidemia) during follow-up, up to seven years post-HCV treatment. Statistical analyses included orthogonal partial least squares discriminant analysis (OPLS-DA), Cox regressions models, and Spearman correlations with inflammation-related biomarkers and immune checkpoint proteins, with multiple comparison corrections using the false discovery rate.Results25% participants developed metabolic events after SVR. OPLS-DA identified 163 lipid species (VIP scores≥1) associated with these events, and adjusted Cox regression confirmed significant associations for 24 of them. Lysophosphatidylcholines (LPCs) were the most prevalent, with higher baseline levels linked to increased metabolic risk. Participants who developed events also had higher levels of plasmalogens LPC (O-LPC), lysophosphatidylethanolamine (LPE), lysophosphatidylinositol (LPI), lysophosphatidic acid (LPA), and phosphosphatidylcholine (PC). Several lipid species correlated positively with the pro-inflammatory cytokine IL-18, the anti-inflammatory suppressor IL-1RA, and the immune checkpoint proteins IDO and S100A8/A9.DiscussionPre-treatment lipid and immune dysregulation was associated with post-SVR metabolic events in HIV/HCV-coinfected participants, suggesting that HCV may leave a lasting metabolic imprint that contributes to adverse outcomes after viral clearance.